Early Symptoms of Patients With COVID-19 in Family Medicine Centers in South India: A Retrospective Study. Issue 1 (June 2020) - Rahman, Sajitha M. F.; Pricilla, Ruby Angeline; Biswas, Arnab; Dharmasivam, Vinodhini; Abraham, Sunil; Sankarapandian, Venkatesan
Introduction: A recent Cochrane review on the diagnostic accuracy of initial signs and symptoms of COVID-19 reported on the lack of evidence from studies conducted in community-based health-care settings. Since a broad spectrum of patients present to primary health-care services, testing for patients with noninfluenza-like illness and atypical presentations is debatable. Hence, there is an urgent need for documenting the early presenting symptoms of COVID-19 among patients seeking medical care in primary health-care settings. Aim: In this study, we aim to document the early symptoms of patients with COVID-19 and the proportion of asymptomatic infection in family medicine centers in South India. Design: This is a retrospective study of the early symptoms of patients who tested positive between June and December 2020. The data and clinical notes of patients were retrieved from the hospital information system. Setting: This study was undertaken by the Department of Family Medicine (DFM) in a private not-for-profit academic institution in South India. The DFM provides primary and secondary health-care services to nearly 1, 50, 000 patients from the local urban communities. Results: A total of 330 patients were tested for COVID-19 and the study included 94 patients who tested positive. Around 37% participants were asymptomatic. The commonest symptom was fever (58.6%), followed by tiredness/myalgia (48.3%), loss of taste or smell or appetite (43.1%), and cough or cold (37.9%). Most participants (78.2%) were hospitalized and the rest (21.8%) were home-quarantined. Only 5 (5.7%) of them died due to COVID-19 infection. Conclusion: The results of the study reiterates the role of social distancing, self-isolation, proper masking, and greater vaccination coverage as significant public health interventions.